Asymptotic Analysis of MMPP/M/1 Retrial Queueing System with Unreliable Server; Communications in Computer and Information Science; Vol. 1605 : Information Technologies and Mathematical Modelling. Queueing Theory and Applications ( ITMM 2021) - Voronina N. M. Natalia Mikhailovna (2022, 2022)
Title screen